Emerging technologies for authorization and authentication : first International Workshop, ETAA 2018, Barcelona, Spain, September 7, 2018, Proceedings /: first International Workshop, ETAA 2018, Barcelona, Spain, September 7, 2018, Proceedings. (2018) - Unknown
No abstract available